The Impact of Environmental Pollution Caused by Human activities and Overcome - Zulfikar, Riyan; Arianti, Nisha Desfi; Mardalena, Tri (WAHANA, 2026)
This study analyzes the impact of environmental pollution caused by human activities and how to mitigate it. The study used qualitative methods. The results revealed four types of human activities that cause pollution: industry, transportation, agriculture, and households. The findings, industrial sector pollution includes exhaust emissions, liquid waste, and solid waste. Transportation includes air pollution from vehicle emissions, water pollution from fuel spills, and soil pollution from vehicle waste. Agriculture includes excessive use of chemicals and livestock waste. Households include domestic waste, wastewater, and emissions from fuel or garbage combustion. Mitigation measures are reviewed through three aspects: air, water, and land. Several researchers' findings indicate that appropriate mitigation measures include the application of environmentally friendly technologies, proper waste management, strengthening regulations, and increasing public awareness through education and active participation